Functional Characterization of a Variant Factor XII (F XII Locarno) in a Cross Reacting Material Positive F XII Deficient Plasma - Wuillemin, Walter A; Furlan, Miha; Stricker, Hans; Lämmle, Bernhard (Thrombosis and Haemostasis, 1992)
The plasma of a healthy woman was found to contain half normal factor XII (FXII) antigen level (0.46 U/ml) without any FXII clotting activity (<0.01 U/ml). The variant FXII in this plasma, denoted as FXII Locarno, was partially characterized by immunological and functional studies on the proposita’s plasma. FXII Locarno is a single chain molecule with the same size (Mr = 80 kDa) as normal FXII. Isoelectric focusing suggested an excess of negative charge in the variant FXII as compared to normal FXII. In contrast to FXII in normal plasma, FXII Locarno was not proteolytically cleaved upon prolonged incubation of proposita’s plasma with dextran sulfate. Adsorption to kaolin was similar for both, abnormal and normal FXII. Incubation of the proposita’s plasma with dextran sulfate and exogenous plasma kallikrein showed normal cleavage of FXII Locarno outside of the tentative disulfide loop Cys340-Cys467, but only partial cleavage within this disulfide loop. Furthermore, plasma kallikrein-cleaved abnormal FXII showed neither amidolytic activity nor proteolytic activity against factor XI and plasma prekallikrein.These results suggest a structural alteration of FXII Locarno, affecting the plasma kallikrein cleavage site Arg353-Val354 and thus formation of activated FXII (a-FXIIa).